MINOS the main injector neutrino oscillation search - Weber, A (2001)
MINOS is a neutrino experiment which uses a beam of neutrinos from the Fermilab main injector to determine the parameters of possible neutrino oscillations. It consists of two detectors: a near detector to measure the beam composition at the production site and a far detector 730 km away to re-measure the composition and detect any oscillation which may have occurred. MINOS is a tracking calorimeter build from solid plastic scintillators to measure all the neutrino interactions.